An attempt of digitalization Bali Strait purse seine capture fisheries data. Issue 1 (February 2021) - Natsir, M; Waryanto,; Wada, M
Abstract: Similar situations with most small-scale fisheries globally, data collection remains the most highlighted issues in Bali sardine purse seine fishery. Nowadays, one of the promising approaches in fisheries data monitoring is through a technological application. This study attempts to conduct the digitalization of capture fisheries data through a tablet application development and implementation, namely MICT-L. It develops since June 2018 based on an existing paper recorder system and operated by the fishing-port officer. MICT-L was fully established in November 2018 in Muncar and September 2019 in Pengambengan fishing port, and this system has been collected and store digital landing data successfully. In addition to the initiation, a GPS-trackers system, namely TREKFISH, was installed in November 2019 and successfully collected fishing ground position data from 19 vessels until February 2020. During the study, a total of 8, 248 landings in Muncar and 6, 598 landings in Pengambengan were collected and stored accordingly. MICT-L and TREKFISH data successfully support the faster near real-time statistical analysis and spatial grid productivity. These two initiations are potent tools for collecting and visualizing digital catch data and fishing grounds for Bali purse seine fisheries.